RE-TURNING INWARDS OR OPENING TO THE WORLD? LAND USE TRANSITIONS ON AUSTRALIA'S WESTERN COAST. Issue 3 (27th May 2022) - Jones, Roy; Jones, Tod; Ingram, Colin
ABSTRACT: Prior to European Settlement in 1829, the Western Australian coast to the north of Perth, the state capital, had long been occupied by the Yued Nyungar Aboriginal group. However, much of this land had limited agricultural potential and, following Aboriginal dispossession, it remained as largely unoccupied Crown (public) Land for about a century. From the 1920s, farmers, crayfishers and Perth residents began to establish campsites and shacks for temporary use. However, since the 1960s, pressure has been growing: to develop better access routes and more formal (and legal) coastal/recreational settlements; to offer greater statutory protection to the natural coastal environment; and to acknowledge Aboriginal rights over some areas of Crown Land. This paper analyses the land use transitions experienced in this coastal area, with particular reference to the growing and diversifying external pressures that are being applied to this formerly isolated and currently vulnerable locality.